The Role Management Accounting Information System, and Digital Competencies in Enhancing Managerial Performance - Ritonga, Mulkan; Rafika, Mulya; Muti'ah, Rahma; Zufrie (Institut Bisnis dan Informatika Kesatuan, 2025)
The development of digital technology has resulted in substantial changes to the organization’s management system, including management accounting. Through the use of digital competency moderation and mediation by the management accounting information system, this study seeks to investigate how managerial performance is affected by digital transformation. This work employs a quantitative methodology using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) analysis technique. The 63 respondents in the sample were managers, proprietors, and organizational leaders of occupational work units, businesses, and MSMEs in Labuhanbatu. Data processing results demonstrate that managerial performance is positively and significantly impacted by digital transformation. An efficient information system increases the influence of digital transformation on enhancing management performance, according to the findings, which also indicate that the management accounting information system acts as a partial mediator in the relationship. Furthermore, it has been demonstrated that the relationship between digital transformation and management accounting information systems is moderated by digital competencies, with higher levels of digital capabilities enhancing the efficacy of system implementation. These findings have significant ramifications, as the preparedness of information systems and the digital capabilities of human resources play a major role in how well digital transformation improves managerial performance.